2023
DOI: 10.3390/ijms24032461
|View full text |Cite
|
Sign up to set email alerts
|

Microbiome Alterations in Alcohol Use Disorder and Alcoholic Liver Disease

Abstract: Microbiome alterations are emerging as one of the most important factors that influence the course of alcohol use disorder (AUD). Recent advances in bioinformatics enable more robust and accurate characterization of changes in the composition of the microbiome. In this study, our objective was to provide the most comprehensive and up-to-date evaluation of microbiome alterations associated with AUD and alcoholic liver disease (ALD). To achieve it, we have applied consistent, state of art bioinformatic workflow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 58 publications
(68 reference statements)
1
7
0
Order By: Relevance
“…Individuals with AUD are often reported to have lower alpha diversity as compared with healthy controls 46,47 but this is not always the case. 17,27 There is even less consensus on the relationship between AUD severity and alpha diversity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Individuals with AUD are often reported to have lower alpha diversity as compared with healthy controls 46,47 but this is not always the case. 17,27 There is even less consensus on the relationship between AUD severity and alpha diversity.…”
Section: Discussionmentioning
confidence: 99%
“…Both acute and chronic alcohol consumption are linked to a shift in microbiome composition favoring an overrepresentation of proinflammatory microbes and an underrepresentation of short-chain fatty acid-producing microbes. [11][12][13][14][15][16][17] During periods of heavy alcohol consumption, the production of short-chain fatty acids (SFCAs) are significantly decreased. 11,16,18 These microbially-produced SCFAs influence various biological processes such as depression, anxiety, and craving, [19][20][21][22][23] which are common comorbidities of AUD.…”
Section: Introductionmentioning
confidence: 99%
“…Alcohol use disorder (AUD) is one of the most significant preventable contributors to morbidity and mortality ( 59 , 60 ). Alcohol directly alters the permeability of the intestinal barrier, causes dysbiosis, and is associated with peripheral and central inflammation ( 60 ).…”
Section: Stress Psychopathology and The Microbiomementioning
confidence: 99%
“…found that individuals with AUD demonstrated lower abundance of Akkermansia muciniphilia and Faecalibacterium prausnitzii , less of the genus Bacterioides, at the phylum level more Pseudomonadota (formerly Proteobacteria), and more members of the Enterobacteriaceae family ( 61 ). A recent study by Litwinowicz & Gamian compared the microbiomes of participants with AUD, alcoholic liver disease (ALD), and healthy controls ( 59 ).…”
Section: Stress Psychopathology and The Microbiomementioning
confidence: 99%
“…A metagenomic analysis in AUD patients by Litwinowicz et al [ 55 ] (concluded to a significant increase in facultative anaerobes (such as the Enterobacteriaceae family), that may be a result of a simultaneous decrease in levels of butyrate-producing bacteria (Butyricicoccaceae, Lachnospiraceae, Ruminococcaceae, Oscillospiraceae), thus reducing beta-oxidation, which in turn ends up increasing oxygen levels. Most of the produced butyrate gets used up for energy, with only approximately 5% remaining in circulation, however, this small fraction appears to be capable of inducing a potent anti-inflammatory response, through various pathways, including through the G-protein-coupled receptors 41 and 43[ 56 ], inhibition of IFN-γ signaling, and induction of nuclear factor kappaB[ 57 ].…”
Section: The Composition Of Gut Microbiome In Healthy Vs Aud Individualsmentioning
confidence: 99%